On rigid derivations in rings - Artemovych, O.D.; Lukashenko, M.P. (Carpathian Mathematical Publications, 2014)
We prove that in a ring $R$ with an identity there exists an element $a\in R$ and a nonzero derivation $d\in Der R$ such that $ad(a) eq 0$. A ring $R$ is said to be a $d$-rigid ring for some derivation $d \in Der R$ if $d(a)=0$ or $ad(a) eq 0$ for all $a \in R$. We study rings with rigid derivations and establish that a commutative Artinian ring $R$ either has a non-rigid derivation or $R=R_1\oplus … \oplus R_n$ is a ring direct sum of rings $R_1,… ,R_n$ every of which is a field or a differentially trivial $v$-ring. The proof of this result is based on the fact that in a local ring $R$ with the nonzero Jacobson radical $J(R)$, for any derivation $d\in Der R$ such that $d(J(R))=0$, it follows that $d=0_R$ if and only if the quotient ring $R/J(R)$ is differentially trivial field.